Pengaruh Komposisi Air Laut dan Pasir Laut Sebagai Sumber Energi Listrik - Okky Putri Prastuti (Politeknik Negeri Malang, 2017)
Electrical energy is energy derived from electric charge that causes static electric field or the movement of electrons in a conductor (conductor of electricity) or ions (positive or negative) in a liquid or gas. The electrical energy needed by society to lighting, heating, cooling, or to move back in mechanical equipment to produce other forms of energy. Utilization of a mixture of sand and sea water is one of the methods of renewable energy. In other hand, utilization of sea water is known that it can generate electricity. This study is a preliminary study to combine sea water and sea sand as raw materials. The purpose of this study was to analyze the optimal composition of sea water and sea sand in generating electrical energy. Source of sea water and sea sand comes from Kenjeran Beach Surabaya Indonesia. Research methods such as mixing sea water and sea sand with a weight percent ratio sea sand in the mixture of 0%, 25%, 50%, 75%, and 100%. The electrical energy generated is determined by observing the current flow and power are seen on the multi meter. Based on the results of current and voltage measurements obtained respectively 2,4 V; 2,3 V; 2,3 V; 1,8 V; and 0,9 V. So the results of the analysis of the composition of sea water and sea sand can potentially be used as a source of electrical energy, although sea sand as agent of resistant.